1992
DOI: 10.1002/j.1460-2075.1992.tb05303.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of Ha-ras p21 that define important regions for the molecular mechanism of the SDC25 C-domain, a guanine nucleotide dissociation stimulator.

Abstract: The SDC25 C‐domain is a very active guanine nucleotide dissociation stimulator (GDS) isolated from Saccharomyces cerevisiae which acts equally well on Ha‐ras p21 and yeast RAS2. These properties make the SDC25 C‐domain a suitable tool to study the basic mechanism of a GDS. The action of the SDC25 C‐domain was analysed by mutation of structurally important regions of p21. Substitutions that influence the coordination of Mg2+.GDP or the interaction of the guanine ring were found to stimulate the intrinsic dissoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
77
1
2

Year Published

1995
1995
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 49 publications
10
77
1
2
Order By: Relevance
“…The last 23 aa of Ras have been shown to be dispensable for binding, in agreement with the results reported here for the Rab3a-Mss4 interaction (24,25). However, a mutational analysis of Ras has shown that the switch II domain (which consists of L4/␣2), but not the switch I domain, is important for binding to its GEFs (26 -28).…”
Section: Discussionsupporting
confidence: 81%
“…The last 23 aa of Ras have been shown to be dispensable for binding, in agreement with the results reported here for the Rab3a-Mss4 interaction (24,25). However, a mutational analysis of Ras has shown that the switch II domain (which consists of L4/␣2), but not the switch I domain, is important for binding to its GEFs (26 -28).…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, these two GEFs are inactive on other Ras-related proteins . Chimeric proteins between the two carboxy domains of Sdc25p and Cdc25p are active GEF on Ras proteins, whereas chimeric proteins between Sdc25p and Bud5p, the specific GEF for Budl/Rsrlp, are inactive proteins (Camus et al, 1994 (Mistou et al, 1992;Haney and Broach, 1994;Jacquet et al, 1995). The Sos GEFs have a low specific activity in vitro on unprocessed Ras proteins.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21] Other, older reports have analyzed the interaction of the protooncogenic effector domain mutants with various guanine exchange factors and GTPase activating proteins. [22][23][24][25] In addition, mutating the highly conserved cysteine at position 186 of the CAAX box domain to serine results in a nonfarnesylated protein that fails to associate with membranes and becomes cytosolic. 26,27 Localization to the membranes and transforming activity of oncogenic Ras/S186 are rescued when Ras is targeted to the membranes by a myristoylation signal in its N-terminal domain.…”
mentioning
confidence: 99%